Kebijakan Pemerintah Provinsi dalam Mencegah Penyebaran Radikalisme sebagai Upaya Menanggulangi Peperangan Asimetris: Studi Kasus di Provinsi Jawa Tengah - Mochammad Afifuddin; Ahmad G. Dohamid; Galang Setyawan Aji (UNIB Press, 2025)
This research aims to find out about the policies of the Central Java Provincial Government in spreading Radicalism which is important in asymmetric warfare. Asymmetric warfare can occur due to technological advances that are increasingly developing now. The Central Java Provincial Government has made many efforts to tackle radicalism, one of which is Governor Regulation No. 35 of 2022 and many other efforts have been made. Implementation of the policies carried out and the role of the government in creating a safe environment from radicalism. The data sources used are literature, journals, scientific articles, and also websites that are appropriate to this research. There are many challenges that Central Java Province still has to face to prevent this radicalism. Keyword: Provincial Government Policy, Radicalism, Asymmetric Warfare, Central Java Province